2022
DOI: 10.3390/pharmaceutics15010145
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Antibody-Based Therapeutics for Cerebral Ischemia

Abstract: Cerebral ischemia is an acute disorder characterized by an abrupt reduction in blood flow that results in immediate deprivation of both glucose and oxygen. The main types of cerebral ischemia are ischemic and hemorrhagic stroke. When a stroke occurs, several signaling pathways are activated, comprising necrosis, apoptosis, and autophagy as well as glial activation and white matter injury, which leads to neuronal cell death. Current treatments for strokes include challenging mechanical thrombectomy or tissue pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 185 publications
0
3
0
Order By: Relevance
“…The availability of novel adjuvant neuroprotective tools may lead to a paradigm shift in stroke therapy [ 19 ]. Recent evidence has indicated that monoclonal antibodies targeting an endogenous molecule or signaling cascade would reduce the severity of the damaged brain tissue; however, the clinical evidence for stroke therapy is minimal [ 20 ]. Although monoclonal antibody therapy has proven effective and safe in treating various neurological disorders in animal studies, the complete antibody cannot cross the blood–brain barrier (BBB), and immunogenicity is a significant limitation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of novel adjuvant neuroprotective tools may lead to a paradigm shift in stroke therapy [ 19 ]. Recent evidence has indicated that monoclonal antibodies targeting an endogenous molecule or signaling cascade would reduce the severity of the damaged brain tissue; however, the clinical evidence for stroke therapy is minimal [ 20 ]. Although monoclonal antibody therapy has proven effective and safe in treating various neurological disorders in animal studies, the complete antibody cannot cross the blood–brain barrier (BBB), and immunogenicity is a significant limitation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has indicated that monoclonal antibodies targeting an endogenous molecule or signaling cascade would reduce the severity of the damaged brain tissue; however, the clinical evidence for stroke therapy is minimal [ 20 ]. Although monoclonal antibody therapy has proven effective and safe in treating various neurological disorders in animal studies, the complete antibody cannot cross the blood–brain barrier (BBB), and immunogenicity is a significant limitation [ 20 ]. Many studies are currently devoted to ascertaining safer and more effective therapies for ischemic stroke to meet clinical needs, and stem cell based ischemic stroke therapy is a current trend [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, monoclonal antibody therapy is becoming more and more common for the treatment of various diseases such as cancers (Pento, 2017), autoimmune diseases (Arzoo et al, 2002) and neurological disorders (Sun et al, 2023), because of their better performance in terms of specificity, safety and pharmacokinetics, compared to small-molecule chemical drugs. Though a number of monoclonal antibodies were developed targeting signalling cascades and endogenous molecules modulating post-stroke inflammation, neuronal repair and regeneration, and showed beneficial effects in animal studies, none of them is approved for clinical use in stroke.…”
Section: Discussionmentioning
confidence: 99%